Efek Antiinflamasi Ekstrak Kulit Tamarillo: Pemeriksaan Kadar IL-6 Tikus Pasca Induksi Karagenin - Salsabila, Sasya Anursyah; Sudiono, Janti (Fakultas Kedokteran Universitas Trisakti, 2022)
BACKGROUND Inflammation is a protective response of the body to injury by releasing pro-inflammatory cytokines; one of them is interleukin-6 (IL-6). The peeled fruit of Tamarillo or terung belanda (Solanum betaceum Cav.) ethanol extract contains flavonoid compounds that have anti-inflammatory potential. This research was conducted to evaluate the anti-inflammatory effect of terung belanda (Solanum betaceum Cav.) peel fruit ethanol extract on carrageenan-induced Wistar strain rat by measuring the IL-6 level. METHOD Tamarillo (Solanum betaceum Cav.) fruit peel was extracted by maceration methods using 70% ethanol as solvent. The anti-inflammatory was evaluated using 30 rats which were divided into five research groups positive control (diclofenac sodium), negative control (NaCl), and Tamarillo (Solanum betaceum Cav.) fruit peel ethanol extract with a dose of 70mg/kg BW, 140mg/kg BW, and 280mg/kg BW. After the treatment, the rats were injected with carrageenan as an inflammatory inducer. Blood samples were taken at 24, 48 and 72 hours to measure the IL-6 level using the ELISA kit. Statistical analysis used one-way ANOVA with a significant difference as 0.05. RESULTSThe lowest IL-6 levels (13.853 pg/ml) were found in 24 hours at the group of 140 mg/kg BW while in 48 hours at the 280 mg/kg BW group and 72 hours at the 70 mg/kg BW group. In 24 hours, the 140 mg/kg BW group showed lower IL-6 levels than the positive control with a significant difference (p=0.001). CONCLUSION Tamarillo (Solanum betaceum Cav.) fruit peel ethanol extract is effective as an anti-inflammatory material, especially for 24 hours with a dose of 140 mg/kg BW. KEYWORDS: Tamarillo, Solanum betaceum Cav., Peel Fruit, Ethanol Extract, Carrageenin, IL-6